2016
DOI: 10.1242/jeb.148429
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms of Na+ uptake and ammonia excretion by the gill and yolk sac epithelium of early life stage rainbow trout

Abstract: In rainbow trout, the dominant site of Na + uptake (J Na,in ) and ammonia excretion (J amm ) shifts from the skin to the gills over development. Post-hatch (PH; 7 days post-hatch) larvae utilize the yolk sac skin for physiological exchange, whereas by complete yolk sac absorption (CYA; 30 days post-hatch), the gill is the dominant site. At the gills, J Na,in and J amm occur via loose Na + /NH 4 + exchange, but this exchange has not been examined in the skin of larval trout. Based on previous work, we hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…Nakada et al (2007b) showed that the apical Rh glycoprotein Rhcg1 (see Box 1) was expressed in the yolk sac epithelium of zebrafish, and that J amm and the number of Rhcg1-expressing cells on the yolk sac increased in conjunction over development. The expression levels of Rh genes in zebrafish embryos and larvae also increased in parallel with J amm over development (Braun et al, 2009a), and this same phenomenon has been observed in early life stages of trout (Hung et al, 2008;Zimmer et al, 2014b). Additionally, many studies have demonstrated strong evidence of a role for Rh glycoproteins in J amm by larval zebrafish using morpholino gene knockdown (Braun et al, 2009a;Kumai and Perry, 2011;Shih et al, 2008Shih et al, , 2012Shih et al, , 2013.…”
Section: Mechanisms Of Excretionsupporting
confidence: 58%
See 4 more Smart Citations
“…Nakada et al (2007b) showed that the apical Rh glycoprotein Rhcg1 (see Box 1) was expressed in the yolk sac epithelium of zebrafish, and that J amm and the number of Rhcg1-expressing cells on the yolk sac increased in conjunction over development. The expression levels of Rh genes in zebrafish embryos and larvae also increased in parallel with J amm over development (Braun et al, 2009a), and this same phenomenon has been observed in early life stages of trout (Hung et al, 2008;Zimmer et al, 2014b). Additionally, many studies have demonstrated strong evidence of a role for Rh glycoproteins in J amm by larval zebrafish using morpholino gene knockdown (Braun et al, 2009a;Kumai and Perry, 2011;Shih et al, 2008Shih et al, , 2012Shih et al, , 2013.…”
Section: Mechanisms Of Excretionsupporting
confidence: 58%
“…In rainbow trout larvae reared in neutral waters with sufficient Na + (>0.5 mmol l −1 ), J amm and J Na,in increased over development (Fu et al, 2010;Zimmer and Wood, 2015;Zimmer et al, 2014b), and these processes were tightly coupled to one another at the gill, but not the skin (Zimmer et al, 2014b). Cutaneous mechanisms of J amm and J Na,in by larval trout are thus similar to those of zebrafish, where indirect Na + /NH 4 + exchange is absent under comparable conditions.…”
Section: Rainbow Troutmentioning
confidence: 70%
See 3 more Smart Citations